The Influence of Family Interaction and Social Environment on Adolescents’ Understanding of Islamic Religion - Hidayah, Nurul; Widyaningsih, Rini; Berutu, Rolli; Kesumawati, Leni (Yayasan Rahmat Islamiyah, 2025)
This study aims to examine the influence of family interaction and social environment on adolescents’ understanding of Islamic religion. The background of this research is based on the crucial role of the family as the primary source of education, as well as the social environment that shapes adolescents’ character and religiosity. The research method employed a quantitative approach using a survey technique with questionnaires distributed to 120 respondents aged 13–18 years. Data were analyzed using multiple linear regression to determine the extent of the effect of the independent variables on the dependent variable. The findings indicate that family interaction significantly affects adolescents’ understanding of Islam, while the social environment also makes a considerable contribution to shaping their religious attitudes. The conclusion emphasizes that synergy between family and social environment is essential in improving adolescents’ quality of understanding of Islamic religion.